2019
DOI: 10.1021/acscatal.9b03677
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Abnormal NHC Ruthenium Catalyst for Oppenauer-Type Oxidation and Transfer Hydrogenation Reactions

Abstract: The ruthenium complex [Ru­(OAc)­(a-PC)2]Br (3) containing two abnormal NHC ligands is obtained by reaction of Ru­(OAc)2(PPh3)2 (1) with 1-(2-diphenyl­phosphinoethyl)-3-mesityl­imidazolium bromide in the presence of NaOAc. Complex 3 catalyzes the Oppenauer-type oxidation of a number of alcohols at unrivalled reaction rates reaching TOFs up to 550 000 h–1, at low catalyst loadings (S/C higher than 10 000) and using acetone in stoichiometric amounts. Complex 3 is also highly active in the reverse transfer hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…This outstanding result shows that our supported hybrid catalyst possesses an impressive catalytic performance. In addition, compared to other homogeneous and heterogeneous reductants previously presented in the literature, only some elaborated Ru complexes, for example containing chiral phosphines as ligands, [6] overturn our SWNT−NH 2 −Ru . Therefore, our material can be considered as a breaking catalyst taking into account the simple synthetic procedure.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This outstanding result shows that our supported hybrid catalyst possesses an impressive catalytic performance. In addition, compared to other homogeneous and heterogeneous reductants previously presented in the literature, only some elaborated Ru complexes, for example containing chiral phosphines as ligands, [6] overturn our SWNT−NH 2 −Ru . Therefore, our material can be considered as a breaking catalyst taking into account the simple synthetic procedure.…”
Section: Resultsmentioning
confidence: 90%
“…Indeed, different metal‐based homogeneous and heterogeneous TH organometallic catalysts (Fe, Os, Co, Ni, Pd, Au, Rh, Ir and Ru, complexes among others) have been reported where the reduced products can be yielded with excellent performance (Scheme 1a) [5] . Moreover, catalytic parameters close to enzymatic behaviour (Turnover frequencies (TOF) with values as high as 500000 h −1 ) are observed when Ru complexes get on stage [6] . In particular, Ru complexes with a great variety of ligands, such as P ‐, N ‐, O ‐chelating rings or carbenes are reported to own the best catalytic activity, [7] with outstanding activities and catalytic parameters [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Ru-catalyzed Oppenauer oxidation is well precedent in the literature. 24 Some of these reactions are known to proceed via the intermediacy of ruthenium-hydrido species, 24a,c,f,j that is also derivable in situ from [Ru(dppbz)(CO) 2 Cl 2 ]. We planned to explore catalytic potential of [Ru(dppbz)(CO) 2 Cl 2 ] towards Oppenauer-type oxidation of secondary alcohols, a green oxidation protocol that utilizes acetone as hydrogen acceptor.…”
Section: Catalytic Transfer-hydrogenationmentioning
confidence: 99%
“…It has recently been found that ruthenium complexes can selectively catalyze such selective hydrogenations. 5 Various ruthenium-catalyzed hydrogenations have been reported, such as hydrogenation of internal alkynes to obtain (E)-alkenes through trans-delivery of hydrogen, 6 hydrogenation of unsaturated aldehydes and carboxylic acids to unsaturated alcohols, 7 enantioselective hydrogenation of hydrazones, 8 and levulinic acid hydrogenation to -valerolactone. 9 Furthermore, ruthenium metathesis can be coupled with selective hydrogenation in a one-pot sequential protocol.…”
Section: Scheme 1 Three Classes Of Ru-based Hydrogenative Metathesismentioning
confidence: 99%